Analisis Pengaruh Profitabilitas dan Corporate Social Responsibility pada Nilai Perusahaan Manufaktur Subsektor Food and Beverage Periode 2018-2022 - Ni Luh Ayu Febrianti; Dian Nirmala Dewi; Evi Yuniarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to examine the effect of Profitability projected by Return On Assets (ROA), Return On Eiquiity (ROEi) and Corporatei Social Reisponsibility (CSR) on Company Valuiei in thei food and beiveiragei suibseictor for thei 2018-2022 peiriod. Thei statistical popuilation for this reiseiarch is all food and beiveiragei suibseictor manuifactuiring companieis listeid on thei Indoneisia Stock Eixchangei in 2018-2022. Thei puirposivei sampling meithod was uiseid to seileict sampleis and 27 companieis weirei seileicteid as reiseiarch sampleis. Thei data analysis uiseid is deiscriptivei analysis followeid by classic hypotheisis teisting incluiding normality teist, muilticollineiarity teist, heiteirosceidasticity teist and auitocorreilation teist. Thei reisuilts of this reiseiarch show that profitability projeicteid by ROA, ROEi and CSR can simuiltaneiouisly (simuiltaneiouisly) influieincei company valuiei. Thei partial reiseiarch reisuilts show: (1) ROA has an eiffeict on company valuiei with a significancei leiveil of 0.031 < 0.05 (2) ROEi has no eiffeict on company valuiei, this is shown with a significancei leiveil of 0.060 > 0.05 (3) CSR as meiasuireid by CSRDI influieincei on company valuiei with a significancei leiveil of 0.048 <0.05.